STRATEGI PENGEMBANGAN PADA KELOMPOK DISABILITAS USAHA MIKRO KECIL MENENGAH BATIK CIPRAT DI DESA KEMUDO KLATEN - Nurmawati, Fathonah; Sayekti, Lulu Anastesi (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
In order to improve the welfare of groups of children with special needs, the Kemudo Village Government collaborated with the Tombo Ati Care Shelter Workshop (SWP) in Kemudo Village to create a UMKM Batik Ciprat with disabilities participants, which is now called Batik Ciprat Tombo Ati Kamajaya. Along the way, there are still various problems, namely (1) Splashed batik products are still less popular with people outside Kemudo Village; (2) The amount of batik production is not yet stable; (3) Promotion via social media and other digital platforms that is not yet optimal; (4) The goal of improving the welfare of people with disabilities through has not yet been achieved. The aim of this research is to determine the development strategy for the UMKM Batik Ciprat disability group in Kemudo Village, Prambanan District, Klaten Regency. The research method used is descriptive qualitative. The results were 14 alternative strategies that could be implemented in the development of disability groups. Of the 14 alternative strategies, there are still several strategies that have not been implemented by UMKM Batik Ciprat Tombo Ari Kamajaya, namely increasing the ability to manage Disability Groups, increasing the quantity and quality of disability groups, using technology in marketing and promotions, as well as joint commitment among stakeholders.Keyword: Development Strategy; Disability Group; Kemudo Village.